2010
DOI: 10.1042/cs20100246
|View full text |Cite
|
Sign up to set email alerts
|

A common polymorphism in theABCB11gene is associated with advanced fibrosis in hepatitis C but not in non-alcoholic fatty liver disease

Abstract: Chronic HCV (hepatitis C virus)-associated cirrhosis represents a major indication for liver transplantation. Bile acids contribute to hepatic stellate cell activation as a key event in fibrogenesis. The aim of the present study was to investigate the role of bile acids and polymorphisms in bile acid level-regulating genes on fibrosis progression. A total of 206 subjects with chronic HCV infection were included for ABCB11 (ATP-binding cassette, subfamily B, member II) 1331T>C and NR1H4 (nuclear receptor) -1G>T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…However, since drug resistant variants are rapidly selected during monotherapy [4], these drugs complement but do not replace the previous IFN-based regimen. HCV patients that have high serum levels of BAs respond poorly to IFN therapy [5] and are more prone to develop hepatic fibrosis [6]. BAs therefore were suggested to play an important role in pathogenesis and therapy response of HCV [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, since drug resistant variants are rapidly selected during monotherapy [4], these drugs complement but do not replace the previous IFN-based regimen. HCV patients that have high serum levels of BAs respond poorly to IFN therapy [5] and are more prone to develop hepatic fibrosis [6]. BAs therefore were suggested to play an important role in pathogenesis and therapy response of HCV [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Europeans researches suggested that the polymorphism of BSEP V444A might be associated with the HCV infection development, liver fibrosis progression and long-term treatment response [811]. The few studies needed to be further supported by researches on extended population.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researches on different related genetic variants have been published [411]. Since 2009, single nucleotide polymorphisms (SNPs) of the interleukin-28B gene have been identified as accurate predictors for therapy response and spontaneous clearance of HCV infection [4, 5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral replication efficiency has been linked to variations in cellular bile salt concentrations using the HCV replicon system [61]. Of note, variants of the human bile salt that export pump ABCB11 might be associated with sustained virological response [62] and progression towards liver cirrhosis [63]. In vitro experiments using HCV replicon-harboring cells have shown that the impact of bile salts on HCV replication might be through the action of FXR rather than a direct effect of bile salts themselves [64].…”
Section: Candidate Receptor Studiesmentioning
confidence: 99%